Students' and teachers' perception of rapport management strategies used by teachers - Sherif, Lobna (AUC Knowledge Fountain, 2020)
The present comparative study explores the perceptions of both students and teachers towards rapport-building behaviors, including the similarities and differences in their respective perceptions of such behaviors. Previous research posits that building rapport in classrooms has been correlated with deeper student engagement and higher motivation towards the course, thereby enabling students to enjoy the learning process itself. An array of rapport- building strategies has been explored, including learning students’ names, showing respect towards the students, and using humor in the classroom. A total of 129 students and 51 teachers filled out a perception questionnaire consisting of 26 teacher traits and behaviors in relation to their importance in building rapport; in addition, the researcher conducted interviews with six language teachers to gain in-depth insight into rapport management in classrooms. Results identified three trends within these 26 behaviors: first, specific behaviors that students perceive as more important than do teachers; second, those behaviors deemed important by both students and teachers; and, third, the behaviors that students perceive as less important in building rapport than do teachers. The results of this study may benefit educators and other stakeholders by raising teachers’ awareness about building rapport in classrooms. The study may also encourage teachers to invest time and effort in activities that students perceive as conducive to rapport- building. In addition, this study could guide program directors to make informed decisions about the hiring of new teachers and renewals for current ones, based on the interpersonal communication skills of each teacher.